Synergy of Charismatic Leadership and Employee Participation in Creating Innovation: Its Impact on Human Resource Effectiveness in the Tourism Sector - Budiman, Dana; Avianto, Irvan; Sutrisno, Slamet; Nadzri, Suhaila binti (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objective: This study aims to analyse the influence of charismatic Leadership and employee participation on human resource management (HRM) effectiveness, with Innovation as a mediating variable. This study was conducted at Amphitheater Ciletuh-Palabuhanratu, part of the UNESCO Global Geopark (UGG), which emphasises sustainable tourism management based on local values.Methodology: The research approach used quantitative methods with an explanatory design. The sample was taken using the total sampling technique, involving the entire population of 100 respondents. Data were collected through a 5-point Likert scale closed questionnaire and analysed using Structural Equation Modeling (SEM) techniques through SmartPLS software.Findings: The results show that charismatic Leadership and employee participation positively and significantly affect Innovation and HR effectiveness. Innovation was also shown to act as a mediating variable in the relationship between the two independent variables and HR effectiveness. The findings confirm that visionary Leadership and employee engagement are key in shaping an innovative and effective work culture.Conclusion: This research provides a practical contribution to formulating innovation-based HRM strategies in sustainable tourism destinations.